TRIM22 promotes glioblastoma development by ubiquitinating Bcl-2 - Jiahao Zhang; Yuning Chen; Gaosong Wang; Hui Huang; Yuankun Liu; Jin Huang; Junfei Shao; Jiantong Jiao; Chao Cheng (Molecular & Cellular Oncology)
Glioblastoma (GBM) exhibits elevated TRIM22 expression correlated with tumor progression, as validated in TCGA/GEO databases. The effects of TRIM22 knockdown and overexpression on GBM proliferation were evaluated with cellular assays. TRIM22 was identified as a potential Bcl-2 activator via a ubiquitination microarray. Flow cytometry (FCM) was utilized to investigate cell apoptosis. Additionally, the expression levels of Bcl-2 and proteins associated with Bcl-2 were evaluated using Western blot analysis. The interaction and ubiquitination of TRIM22 and Bcl-2 were analyzed via immunoprecipitation (IP). TRIM22 overexpression is correlated with glioma progression, and TRIM22 deficiency inhibits GBM cell proliferation. FCM revealed that TRIM22 knockdown promotes GBM cell apoptosis. A TRIM22-overexpressing ubiquitination microarray identified TRIM22 as a potential activator of Bcl-2. Western blot analysis revealed that TRIM22 increases the protein expression levels of Bcl-2. Ubiquitination assays revealed that TRIM22 promotes the stability of Bcl-2 via nondegradative ubiquitination. IP experiments indicated that TRIM22 binds to Bcl-2. TRIM22 may significantly impact glioma progression by modulating Bcl-2. Previous studies have shown that knockdown of TRIM22 can enhance the sensitivity of temozolomide treatment, so TRIM22 is expected to become a new target for glioma immunotherapy.